Cultivation possibility of ashwagandha (Withania somnifera) to promote as a medicinal crop in Jaffna district - Suvanthini, S.; Shyama, T.; Mikunthan, G. (1st Ruhuna International Science and Technology conference,Faculty of Science, University of Ruhuna, 2014)
Ashwagandha (Withania somnifera) is a well reputed medicinal plant. Due to its importance, farmers are interested to cultivate it in larger extent. Present study was aimed to assess the potential of W. somnifera cultivation in Jaffna district, Sri Lanka during the cropping period of August 2011 to June 2012. Different field trials and in vitro studies were conducted. For field trials, Seeds of W. somnifera were sown to evaluate the phenology of the plant. Germination took place 5.6 ± 1.16 days after sowing. Transplanting was done at one month to main field at 45cm × 60cm spacing. Flowering was observed continuously but flowering and fruiting commenced 66.17 ± 3.43 and 79.77 ± 2.07 days after the transplanting, respectively. Harvesting can be done from six to seven month because in this time root: shoot ratio was optimum. The highest dry root yield was obtained at six month which was 58.32g. Seed production of W. somnifera was registered that a plant produced an average of 6581.89 seeds. This number is good enough to get adequate planting material but the germination percentage of W. somnifera generally low due to dormancy. To break down the dormancy, seeds were subjected to water soaking over night and hot water soaking. Highest germination percentage was obtained in hot water soaking that induced 52.75% germination while water soaking resulted 33.75% when compare with control (12.5%). These studies suggest that the climate and soil prevalent in Jaffna are apt to grow this herb with least cost techniques.
Keywords: Withania somnifera; dormancy; germination percentage; Seeds; root shoot ratio